Enhancement in thermoelectric properties due to Ag nanoparticles incorporated in Bi2Te3 matrix - Gupta, Srashti; Agarwal, Dinesh Chandra; Sivaiah, Bathula; Amrithpandian, Sankarakumar; Asokan, Kandasami; Dhar, Ajay; Panigrahi, Binaya Kumar; Avasthi, Devesh Kumar; Gupta, Vinay (Beilstein Journal of Nanotechnology, 2019)
The present study aims to see the enhancement in thermoelectric properties of bismuth telluride (Bi2Te3) annealed at different temperatures (573 and 773 K) through silver (Ag) nano-inclusions (0, 2, 5, 10, 15 and 20 wt %). Transmission electron microscopy (TEM) images of Ag incorporated in Bi2Te3 annealed at 573 K shows tubular, pentagonal, trigonal, circular and hexagonal nanoparticles with sizes of 6–25 nm (for 5 wt % Ag ) and 7–30 nm (for 20 wt % Ag). Ag incorporated in Bi2Te3 annealed at 773 K shows mainly hexagonally shaped structures with particle sizes of 2–20 nm and 40–80 nm (for 5 wt % Ag) and 10–60 nm (for 20 wt % Ag). Interestingly, the samples annealed at 573 K show the highest Seebeck coefficient (S, also called thermopower) at room temperature (p-type behavior) for 5% Ag which is increased ca. five-fold in comparison to Ag-free Bi2Te3, whereas for samples with the same content (5% Ag) annealed at 773 K the increment in thermopower is only about three-fold with a 6.9-fold enhancement of the power factor (S2σ). The effect of size and shape of the nanoparticles on thermoelectric properties can be understood on the basis of a carrier-filtering effect that results in an increase in thermopower along with a control over the reduction in electrical conductivity to maintain a high power factor yielding a high figure of merit.
Keywords: bismuth telluride; nanoparticles; power factor; thermoelectric power